2005
DOI: 10.1136/sti.2004.011999
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for syphilis in antenatal care: compliance with the three dose standard treatment regimen

Abstract: Background: In South Africa, three doses of benzathine penicillin 2.4 MU at weekly intervals are recommended for treating syphilis in pregnancy. Limited information is available on compliance with the recommended regimen, in terms of time to starting treatment, number of doses, and timing of treatment. Methods: The study was conducted to establish the degree of compliance with treatment for syphilis. Timing of treatment and the titres of the rapid plasma reagin (RPR) positive women were recorded. A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
11
2
1
Order By: Relevance
“…These differences could be due to the better health system in Khartoum as opposed to that in Juba which is yet to be established to support maternal and child health. The prevalence results from this current study are different from those found by other workers who found very low rates ranging from a low of 0% in Kabul, Afghanistan (11), 0.9% in a suburban community in Northern Sudan (12) and 1.03% in South Africa (13). Other low prevalence of 4.0% in pregnant women has been found in Entebbe, Uganda (14).…”
Section: Discussioncontrasting
confidence: 56%
“…These differences could be due to the better health system in Khartoum as opposed to that in Juba which is yet to be established to support maternal and child health. The prevalence results from this current study are different from those found by other workers who found very low rates ranging from a low of 0% in Kabul, Afghanistan (11), 0.9% in a suburban community in Northern Sudan (12) and 1.03% in South Africa (13). Other low prevalence of 4.0% in pregnant women has been found in Entebbe, Uganda (14).…”
Section: Discussioncontrasting
confidence: 56%
“…The high prevalence rates of syphilis among the more rural north-western women compared to their urban counterparts in the north-eastern part might be attributable to low education levels, limited access to health care and high levels of poverty (Yahya-Malima et al, 2008). As a result, the rural areas might lag behind urban areas in terms of treatment adherence as many rural, pregnant women attend late for antenatal care (Mullick et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Syphilis point-of-care (POC) testing is provided as part of the routine antenatal services in South Africa. This was implemented to help improve healthcare access and neonatal health outcomes [7][8][9][10][11]. The introduction of syphilis POC testing has been shown to be effective in strengthening health systems by improving access to quality-assured prenatal screening and saving new-born lives in resource-limited settings [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Syphilis infection has been associated with HIV through facilitating HIV transmission and the combination of syphilis, particularly during pregnancy [9,15]. Early detection of Treponema pallidum and prompt penicillin treatment for pregnant women who test positive have been shown to be effective in reducing adverse pregnancy outcomes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%